Heterotopic ossification of the hip post reamed intramedullary femoral nail: a case report - Kow, Ren Yi; Low, Chooi Leng; Jaya Raj, Jeffrey; VA Abraham, Jacob; Mor Japar Khan, Ed Simor Khan (Crimson Publishers, 2019)
Hetorotopic Ossification (HO) is abnormal formation of bone in the soft tissue. Heterotopic ossification of the hip following reamed interlocking medullary nail is uncommon and it has received little attention from the clinician. We take this opportunity to report a young man who presented with symptomatic heterotopic ossification of the hip eight months post antegrade reamed interlocking medullary nail which failed conservative treatment. Reamed intramedullary nailing and delayed mobilization are the contributing factors in this patient. The pathophysiology of this condition is not fully understood. As a result, there is no consensus in the prevention of heterotopic ossification in such patients. Similarly, the management of this condition also is lacking but resection is the treatment of choice for symptomatic patient.